5th Biennial Conference on Heart Valve Biology and Tissue Engineering 2012
DOI: 10.5339/qproc.2012.heartvalve.4.39
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Suitability of Decellularised Porcine Pericardium for Mitral Valve Reconstruction

Abstract: The aim of this study was to investigate the suitability of decellularised porcine pericardium for heterotopic repair of the mitral valve (MV) leaflets, and its potential to regenerate through endogenous cell repopulation in vivo, or in vitro seeding and bioreactor conditioning. Anterior and posterior MV leaflets and pericardia were excised from porcine hearts within. The pericardia were decellularised according to the in-house protocol. Anterior and posterior leaflet, and decellularised and fresh pericardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
4
18
0
1
Order By: Relevance
“…These findings match similar testing done in bovine pericardium that showed that the UTS of native and fixed pericardium was over 50% stronger than native cusps (Arbeiter, Grabow, Wessarges, Sternberg, & Schmitz, 2012). Additionally, our decellularized tissues showed similar UTS to those reported (Morticelli, Korossis, Thomas, Roberts, & Ingham, 2013); yet we observed anisotropy in our material as is seen in other published literature (Gauvin et al, 2012;Labrosse et al, 2016). Our results show that the decellularization process lowers the GAGs compared with the native scaffolds (Figure 3), likely due to the caustic nature of SDS.…”
Section: Discussionsupporting
confidence: 91%
“…These findings match similar testing done in bovine pericardium that showed that the UTS of native and fixed pericardium was over 50% stronger than native cusps (Arbeiter, Grabow, Wessarges, Sternberg, & Schmitz, 2012). Additionally, our decellularized tissues showed similar UTS to those reported (Morticelli, Korossis, Thomas, Roberts, & Ingham, 2013); yet we observed anisotropy in our material as is seen in other published literature (Gauvin et al, 2012;Labrosse et al, 2016). Our results show that the decellularization process lowers the GAGs compared with the native scaffolds (Figure 3), likely due to the caustic nature of SDS.…”
Section: Discussionsupporting
confidence: 91%
“…Before testing, all the samples were maintained in PBS at 4 C. Dog-bone shaped (4-mm width and 20-mm height) specimens were dissected from pericardial tissue sheets and no preferential orientation was considered when cutting the specimens, assuming porcine pericardium isotropy. 27 The ends of the specimens were glued with cyanoacrylate adhesive in between of frames made of finegrained emery article to facilitate uniform gripping and to avoid sample slippage. Then the specimens were mounted onto the clamps of the testing machine (MTS hydraulic testing machine equipped with 100-N loading cell, MTS System Corporation) and the sides of the sandpaper frame were cut.…”
Section: Uniaxial Tensile Lading Testsmentioning
confidence: 99%
“…13- 15 Glutaraldehyde fixation has been used to treat both homogeneic and xenogeneic pericardium to reduce immunogenicity, as well as to treat autologous pericardium in order to increases stiffness, making it easier to handle. 16 The disadvantage of chemically treated pericardium is a lack of in vivo regeneration related to the presence of tissue cross-links. 15 In addition, the toxicity of residual glutaraldehyde prevents cellular infiltration, repair, and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Chemically treated autologous and xenogeneic (bovine and porcine) pericardial tissue has been extensively used for aortic and MV reconstructions. 11- 16 Autologous pericardium is preferred because it has several advantages including low cost, lack of donor-derived pathogens, and nonimmunogenic characteristics, although it has disadvantages such as limited availability and inflammatory changes that occur after pericardiotomy. 12 A current biological substitute for autologous human pericardium is glutaraldehyde-fixed…”
Section: Discussionmentioning
confidence: 99%